Experimental Study on Joint of HDPE Pipe with and Without GEO-GRID as Reinforcement - Ratnaraju, Rajkumar; R, Tharani; K, Muthulakshmi; Kamaleswari, Kamaleswari; Kavya, Kavya (Journal of Neonatal Surgery, 2025)
A variety of buried pipe infrastructure is needed to service the needs of our communities. The conduit surrounded by soil is both loaded and supported by the earth and pore water. However the conditions considered in this work pertains to only earth pressure and not poor water pressure. The pipes are broadly classified as Rigid and Flexible. The aim of this project is to study deflection behavior of flexible pipe (HDPE) at the joint.: The experiment was carried out for 4 sets of reading at two different levels (0.4m and 0.8m) of burial with and without Geo-grids at both levels using an experimental set up of model trench (Fabricated steel tank) with desirable material as bedding and backfill, loading provisions to provide uniform loading. The basic concept behind the experiment involves measuring the deflection values of the pipe for different readings using proving ring and dial gauge.: In addition to this, this project aims to study the load deformation behavior of the buried pipe across the cross section (both crown and springing line) of the joints under uniform loading when soil is reinforced with geo-grid reinforcement, and evaluate the structural performance of the pipe and compare the results with theoretical results and infer the findings. Based on the conclusions, various recommendations can be made, in terms of the pipe’s application in place of Conventional pipes and thereby reduce risk of leakage, damage and also compensating the cost of pipe systems, economically as the joints in pipeline are the weakest and most vulnerable.